Annual Summary of Global Infectious Diseases in 2024 - Yinfu Sun; Dongliang Liu; Yufan Wu; Guodan Li; Yi Luo; Qi Xiang; Yan Wu; Xiang Guo; Lin Lin; Taihan Li; Wenjin Yu; Dayong Gu (Zoonoses, 2025)
Infectious diseases pose a major challenge to public health worldwide. In recent years, vector-borne and zoonotic diseases have emerged as major public health threats. Effective prevention, control, and essential monitoring strategies are required to combat the rising global incidence and prevalence of infectious diseases. The frequency of infectious disease outbreaks has increased in the past several decades, and this trend has been predicted to be likely to continue. To effectively identify public health threats, and monitor and alert against infectious diseases, we obtained surveillance data from Shusi Tech’s Global Epidemic Information Monitoring System and conducted a comprehensive analysis of outbreak timing and location from the beginning of the year to December of 2024.